Sex Differences in Mental Health and Substance Use Disorders and Treatment Entry Among Justice-involved Veterans in the Veterans Health Administration. Issue 4 (April 2015) - Finlay, Andrea K.; Binswanger, Ingrid A.; Smelson, David; Sawh, Leon; McGuire, Jim; Rosenthal, Joel; Blue-Howells, Jessica; Timko, Christine; Blodgett, Janet C.; Harris, Alex H. S.; Asch, Steven M.; Frayne, Susan
Abstract : Background: Over half of veterans in the criminal justice system have mental health or substance use disorders. However, there is a critical lack of information about female veterans in the criminal justice system and how diagnosis prevalence and treatment entry differ by sex. Objectives: To document prevalence of mental health and substance use disorder diagnoses and treatment entry rates among female veterans compared with male veterans in the justice system. Research Design: Retrospective cohort study using national Veterans Health Administration clinical/administrative data from veterans seen by Veterans Justice Outreach Specialists in fiscal years 2010–2012. Subjects: A total of 1535 females and 30, 478 male veterans were included. Measures: Demographic characteristics (eg, sex, age, residence, homeless status), mental health disorders (eg, depression, post-traumatic stress disorder), substance use disorders (eg, alcohol and opioid use disorders), and treatment entry (eg, outpatient, residential, pharmacotherapy). Results: Among female veterans, prevalence of mental health and substance use disorders was 88% and 58%, respectively, compared with 76% and 72% among male veterans. Women had higher odds of being diagnosed with a mental health disorder [adjusted odds ratio (AOR)=1.98; 95% confidence interval (CI), 1.68–2.34] and lower odds of being diagnosed with a substance use disorder (AOR=0.50; 95% CI, 0.45–0.56) compared with men. Women had lower odds of entering mental health residential treatment (AOR=0.69; 95% CI, 0.57–0.83). Conclusions: Female veterans involved in the justice system have a high burden of mental health disorders (88%) and more than half have substance use disorders (58%). Entry to mental health residential treatment for women is an important quality improvement target. Abstract : Supplemental Digital Content is available in the text.